2006
DOI: 10.1073/pnas.0510748103
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax lethal factor and edema factor act on conserved targets in Drosophila

Abstract: Many bacterial toxins act on conserved components of essential host-signaling pathways. One consequence of this conservation is that genetic model organisms such as Drosophila melanogaster can be used for analyzing the mechanism of toxin action. In this study, we characterize the activities of two anthrax virulence factors, lethal factor (LF) and edema factor, in transgenic Drosophila. LF is a zinc metalloprotease that cleaves and inactivates most human mitogen-activated protein kinase (MAPK) kinases (MAPKKs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…The transcription factor cAMP response binding protein (CREB), which is a downstream target of cAMP signaling activated via phosphorylation by protein kinase A (PKA) (31), is activated in macrophages exposed to ET (19,22,27). Conversely, using a Drosophila model, Guichard and colleagues found that EF activates hedgehog signaling in a PKA-dependent manner (14). The possible impact of ET intoxication on mitogen-activated protein kinases is not fully resolved, as Paccani et al also reported that ET can inhibit mitogen-activated protein and stress kinase responses in T lymphocytes (26); however, in a separate study, Comer et al did not detect a similar effect in T lymphocytes isolated from mice treated with ET (5).…”
mentioning
confidence: 99%
“…The transcription factor cAMP response binding protein (CREB), which is a downstream target of cAMP signaling activated via phosphorylation by protein kinase A (PKA) (31), is activated in macrophages exposed to ET (19,22,27). Conversely, using a Drosophila model, Guichard and colleagues found that EF activates hedgehog signaling in a PKA-dependent manner (14). The possible impact of ET intoxication on mitogen-activated protein kinases is not fully resolved, as Paccani et al also reported that ET can inhibit mitogen-activated protein and stress kinase responses in T lymphocytes (26); however, in a separate study, Comer et al did not detect a similar effect in T lymphocytes isolated from mice treated with ET (5).…”
mentioning
confidence: 99%
“…A zebrafish model of vascular collapse also implicated endothelial cells as the target for LT action [301]. In Drosophila, overexpression of either toxin inhibited Rab11/Sec15 endocytic recycling and the Notch signaling [302,303] that is required for cadherin expression at cell junctions, possibly suggesting increased permeability due to altered cell-to-cell junctions.…”
Section: Late Systemic Effects and Vascular Collapsementioning
confidence: 99%
“…Guichard et al (3) report that there are no receptors onto which PA anthrax toxin can bind encoded in the Drosophila genome. However, it is clear from this study that Drosophila can still be used for studying the effects of the anthrax toxins.…”
Section: The Use Of Toxins In Drosophilamentioning
confidence: 99%
“…Most importantly, Guichard et al's study (3) shows that LF and EF function on evolutionarily conserved pathways and provides the platform for secondsite modifier genetic screens. Overexpression of toxins in tissues dispensable for viability of the fly, such as the eye or the wing, create a sensitized genetic background in which mutations that will suppress and͞or enhance the toxins' effect can be readily identified.…”
Section: The Use Of Toxins In Drosophilamentioning
confidence: 99%